Mother tongue-based multilingual education guide for teacher educators and students : mother tongue Filipino English - Young, Catherine; Wilson, Michael I.; McEacherm, Firth; Skoropinski, Zinia R.; Dekker Diane; Giron, Paraluman R.; Flojo, Ofelia O.; Japson, Magdalena R.; Bañez,Ruby Catherine G.; Corpuz, Brenda B. (Quezon City Lorimar Publishing, Inc., 2016)
"This teaching guide is intended for teacher educators and Education students for the subject teaching the Mother Tongue/Mother Tongue-Based Multilingual Education offered in the College of Education. It is also meant for basic education teachers who teach in the Mother-Tongue and who teach Mother Tongue as a subject"--Preface.
Includes bibliographical references and index.
Keywords: Native language and education -- Philippines; Multilingualism -- Philippines; English language -- Study and teaching (Primary) -- Philippines; Education, Primary -- Philippines